2022
DOI: 10.1590/1984-0462/2022/40/2021134in
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 cutaneous manifestations in children and adolescents: a systematic review

Abstract: Objective: The aim of this study was to evaluate the coronavirus disease 2019 (COVID-19) cutaneous manifestations described in pediatric patients and discuss their relevance for early diagnosis. Data source: The study consisted of a systematic review of original articles indexed in PubMed and Embase databases, as well as gray literature articles found through Google Scholar. A search strategy, based on PICO (Patient, Intervention, Comparison, Outcome) Tool, with the terms “child,” “infant,” “childhood,” “adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Macular lesions were also the predominant skin manifestations observed in SARS-CoV-2-positive children, followed by erosions [12,14,26,27]. In agreement, Shah et al [14] showed that most pediatric subjects had erythematous maculopapular skin eruptions, which are often the typical dermatological manifestation of viral infections, although their distribution was not typically cephalocaudal as in other viral exanthemas.…”
Section: Sars-cov-2 Infection In Pediatric Subjectsmentioning
confidence: 64%
See 2 more Smart Citations
“…Macular lesions were also the predominant skin manifestations observed in SARS-CoV-2-positive children, followed by erosions [12,14,26,27]. In agreement, Shah et al [14] showed that most pediatric subjects had erythematous maculopapular skin eruptions, which are often the typical dermatological manifestation of viral infections, although their distribution was not typically cephalocaudal as in other viral exanthemas.…”
Section: Sars-cov-2 Infection In Pediatric Subjectsmentioning
confidence: 64%
“…After duplicate elimination, those records not compliant with the eligibility criteria were excluded. Ten studies [3,[10][11][12][13][14][15][16][17][18] exclusively involved SARS-CoV-2-positive pediatric (<18 years old) cases with oral lesions and/or pediatric subjects with oral lesions after at least one administration of the COVID-19 EMA-authorized [8] and WHO Emergency Use Listing-approved vaccines [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another review including 34 studies around the world showed that acral lesions were the most common category identified (40.4% of all cases), followed by erythematous maculopapular rashes (21.3%), vesicular rashes (13.0%), urticarial rashes (10.9%), other ill‐defined rashes (4.3%), vascular rashes within the spectrum of livedo/purpura/necrosis (4%), erythema multiforme‐like eruptions (3.7%), and unspecified erythematous rashes (2.1%) 17 . Finally, a review of 369 children and adolescents with cutaneous manifestations found that the most common COVID‐19 cutaneous symptoms in this age group were chilblain‐like lesions (67.5%), followed by erythema multiforme‐like (31.7%) and to a varying degree varicella‐like lesions (0.8%) 18 . This appraisal of published literature showed that gathering dermatology‐related data about geographical differences in the morphology and prevalence of reported COVID‐19‐associated cutaneous manifestations is essential in each country and region, particularly on the African continent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…17 Finally, a review of 369 children and adolescents with cutaneous manifestations found that the most common COVID-19 cutaneous symptoms in this age group were chilblain-like lesions (67.5%), followed by erythema multiforme-like (31.7%) and to a varying degree varicella-like lesions (0.8%). 18 This appraisal of published literature showed that gathering dermatology-related data about geographical differences in the morphology and prevalence of reported COVID-19-associated cutaneous manifestations is essential in each country and region, particularly on the African continent.…”
Section: Literature Reviewmentioning
confidence: 99%